Markers for predicting the efficacy of beta-blockers in vasovagal syncope management in children: A mini-review - Jing Wang; Xueqin Liu; Hongfang Jin; Junbao Du; Junbao Du (Frontiers in Cardiovascular Medicine, 2023)
Vasovagal syncope (VVS) is a common subtype of neurally mediated syncope. It is prevalent in children and adolescents, and critically affects the quality of life of patients. In recent years, the management of pediatric patients with VVS has received extensive attention, and β-blocker serves as an important choice of the drug therapy for children with VVS. However, the empirical use of β-blocker treatment has limited therapeutic efficacy in patients with VVS. Therefore, predicting the efficacy of β-blocker therapy based on biomarkers related to the pathophysiological mechanism is essential, and great progress has been made by applying these biomarkers in formulating individualized treatment plans for children with VVS. This review summarizes recent advances in predicting the effect of β-blockers in the management of VVS in children.